What determines foreign direct investment in Russia? - Oleg Gurshev (Central European Economic Journal (CEEJ), 2019)
This article focuses on the determinants of inward foreign direct investment (FDI) in Russia. The article briefly describes the historical context of foreign investment policymaking in Russia since the beginning of the economic transition to an open market economy after the dissolution of the Soviet Union. When compared to other developing countries, Russia's FDI stocks continue to lag despite a set of proactive measures undertaken by the national government. Following the literature review, the most commonly cited determinants explaining inward FDI in Russia include market size, labour productivity, trade and investment barriers, domestic exchange rate, rule of law and institutional framework. This article aims to contribute empirically to the study of determinants of inward FDI in Russia. This article uses the Pseudo-Poisson Maximum Likelihood (PPML) estimation technique, the robustness of the PPML estimation is then verified using a standard autoregressive integrated moving average (ARIMA) model with the Durbin-Watson autocorrelation test. Our benchmark results suggest the efficiency-seeking motive of FDI over a market seeking and horizontal motive as a main reason for inward FDI in Russia. The ARIMA regression indicates the absence of statistical significance of economic openness and variables of labour productivity. Overall, the market size and tax rate variables have the most positive effects on the inward FDI, while barriers to trade and sanctions have the most negative effects. The results confirm that for transitional economies, integration into the world economy, proactive local development and tax cuts for outside investors remain to be critical when it comes to attracting FDI.
Keywords: F23; P33; 330; foreign direct investment; economic transition; Russia